Hallucinatory altered states of consciousness as virtual realities - Móró, Levente (fi=Turun yliopisto|en=University of Turku|, 2017)
The purpose of this doctoral thesis is to investigate altered states of consciousness (ASC) that are marked by hallucinations, occur during hypnosis, or are induced by psychedelic drugs. A multidisciplinary approach is used for enabling the integration of methods and results from various fields of human sciences, such as psychology and phenomenology. The included four studies focus on significant changes occurring in the human mind during deliberately induced, first-person reportable, non-ordinary subjective experiences. Theoretical issues concern the definition and classification of altered consciousness, while empirical research approaches the phenomena with an experimental study on hypnosis and sleepiness, and an online study on psychedelic drug use. Study I ("Hallucinatory Altered States of Consciousness") is a theoretical analysis that proposes a working definition of hallucinatory ASC based on objectively detectable and subjectively experienced changes in neurocognitive subsystems. To solve the 'selection–definition ordering problem' (i.e., whether to define ASC by selected phenomena, or to select phenomena as ASC by a definition), a stepwise operationalization procedure is also proposed. Study II ("Hypnotizability, Sleepiness, and Subjective Experience") describes an empirical hypnosis study in 90 subjects by using one newly developed and three previously established self-rating scales. Results indicate that hypnotizability correlates positively with both habitual daytime sleepiness and instantaneous sleepiness after the hypnotic procedure, hence sleep and hypnosis may share common, putatively neurobiological mechanisms regarding transitions between ASC. Study III ("Coping, Life Purpose, and Spirituality in Psychedelic Drug Users") is based on an online questionnaire survey of 667 psychoactive drug users. Findings point out that psychedelic drug use may facilitate the gain of autognosis (self-knowledge) by rehearsing personal coping strategies in exceptional mental situations. As autognostic psychedelic drug use correlates positively with coping and spirituality, it may also act as a protective factor against drug-related problems. Study IV ("Sacramental and Spiritual Use of Hallucinogenic Drugs") is a commentary article arguing that sacramentally and spiritually used psychedelic drugs ('entheogens') are associated with a search of metaphysical insight rather than with a mere need to alter one’s perception. Therefore, ritual and ceremonial use of hallucinogenic drugs deserves its own category in a drug instrumentalization framework: "to facilitate spiritual and religious activities". The thesis utilizes the overarching concept of virtual realism, stating that phenomenal-level consciousness manifests as a world-simulator by which the mind–brain complex experiences its own virtual information processing as subjective reality. Hence, deliberate manipulation of the experience set and setting parameters by psychologically, pharmacologically, and technologically induced hallucinatory ASC can be a naturally integrable and effective method to extend human consciousness.

Tohtorinväitöskirjani tutkii hallusinaatioihin liittyviä, hypnoosin aikana tapahtuvia, tai psykedeelisten aineiden aikaansaamia muuttuneita tajunnantiloja (MTT). Aihetta lähestytään ihmistieteiden eri alojen, kuten psykologian ja fenomenologian, menetelmiä ja tuloksia yhdistävästä monitieteisestä näkökulmasta. Sisällytetyt neljä tutkimusta keskittyvät ihmismielen merkittäviin muutoksiin tahallisesti aikaansaatujen, omasta näkökulmasta kerrottujen, epätavallisten subjektiivisten kokemusten aikana. Teoreettisina aiheina ovat MTT:n määritelmä ja luokitus, käytännön tutkimukset lähestyvät ilmiöitä niin kokeellisen hypnoosi- ja uneliaisuustutkimuksen kuin myös psykedeelisten aineiden käyttöä kartoittavan internet-tutkimuksen menetelmin. Tutkimus n:o 1 ("Hallusinatoriset MTT-t") on teoreettinen analyysi, jossa ehdotetaan neurokognitiivisten alajärjestelmien muutosten objektiivisen havaitsemiseen ja subjektiivisen kokemiseen perustuva MTT-työmääritelmä. Artikkeli ehdottaa myös askeleittaisen operationalisointi-menettelytavan, jolla ratkeaa ns. 'valinta–määritys -järjestysongelma' (eli valitaanko ensin MTT-ilmiöitä MTT-käsitteen määritystä varten, vai määritelläänkö ensin MTT-käsite MTT-ilmiöiden valintaa varten). Tutkimus n:o 2 ("Hypnoosiherkkyys, uneliaisuus, ja subjektiivinen kokemus") on 90 henkilön kokemusperäinen hypnoositutkimus, jossa käytetään yhtä uutta ja kolmea vakiintunutta itsearviointimittaria. Tulokset osoittavat, että hypnoosiherkkyys korreloi positiivisesti sekä tavanomaisen päiväuneliaisuuden että hypnoosin jälkeisen välittömän uneliaisuuden kanssa, mikä viitannee unen ja hypnoosin yhteisiin neurobiologisiin mekanismeihin MTT:jen välisissä siirtymisissä. Tutkimus n:o 3 ("Hallinta, tarkoitus, ja henkisyys psykedeelisten aineiden käyttäjillä") perustuu psykoaktiivisten aineiden 667 käyttäjän internet-kyselyyn. Löydökset osoittavat, että psykedeelisten aineiden käyttö voi edistää itsetuntemusta harjoittamalla henkilökohtaisia hallintatoimintoja mielen poikkeuksellisissa tilanteissa. Tiedostava psykedeelisten aineiden käyttö korreloi positiivisesti hallinnan ja henkisyyden kanssa toimien suojatekijänä aineidenkäytön ongelmia vastaan. Tutkimus n:o 4 ("Hallusinogeenien sakramentaalinen ja hengellinen käyttö") on kommentti-artikkeli, jonka mukaan sakramentaalisesti ja hengellisesti käytetyt psykedeelit (enteogeenit) liittyvät pikemminkin metafyysisten oivallusten etsintään kuin pelkkään havaitsemisen muuttamistarpeeseen. Täten hallusinogeenien rituaalinen ja seremoniallinen käyttö ansaitsee oman kategoriansa aineiden instrumentalisaation viitekehyksessä: "hengellisten ja uskonnollisten toimintojen edesauttaminen". Teos hyödyntää virtuaalisen realismin käsitettä, jonka mukaan fenomenaalisen tason tajunta ilmenee maailma-simulaattorina, jolla mieli–aivot -kokonaisuus kokee oman virtuaalisen tiedonkäsittelynsä subjektiivisena todellisuutena. Kokemusten set ja setting -muuttujien tahallinen manipulointi psykologisesti, farmakologisesti, ja teknologisesti aikaansaatujen hallusinatoristen MTT:jen avulla voi olla luontaisesti yhdistettävä ja tehokas menetelmä ihmistajunnan laajentamiseksi.